EMOTIONAL COMPETENCIES AND PERSONALITY TRAITS OF MANAGERS IN MODERN AGROBUSINESS - Nikić, Gordana; Stamatović, Ljubiša; Sućeska, Azra (Economics of Agriculture, 2017)
The main goal of this paper is to determine the difference between high-level and midlevel managers in agribusiness compared to lower managerial positions in terms of personality traits and emotional intelligence. The research covered 240 respondents from Serbia. The structure of the sample is heterogeneous, consisting of employees and managers of both genders and various ages. This paper presents the results relating to the permanent staff of 125 managers in the Mercator Group trade chain of food industry. To estimate emotional intelligence Questionnaire of emotional competence (Takšić, Moharić, Munjas, 2006) was used, and Personality Questionnaire was used for estimating dominant personality traits, ZKPQ (Zuckerman, 2002). The results indicate that the higher-level managers show a higher level of emotional intelligence in perceiving and understanding emotions, regulation and management of emotions, and also their personality trait called Activity is higher than in any other group of respondents. The respondents who are in lower managerial positions show higher sociability in relation to the higher-level managers.